2020
DOI: 10.2147/jir.s271628
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Encephalitozoon cuniculi</em> Genotype II Concentrates in Inflammation Foci</p>

Abstract: Background: Microsporidia of the genus Encephalitozoon are generally connected with severe infections with lethal outcome in immunodeficient hosts. In immunocompetent hosts, microsporidiosis typically establishes a balanced host-parasite relationship that produces minimal clinically overt disease. Although the alimentary tract represents one of the main primary target tissues, the mechanisms of reaching other tissues during systemic microsporidian infections remain unclear. Methods: In the present study, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 50 publications
3
12
2
Order By: Relevance
“…In SCID mice the concentration of microsporidia was the most intense in E. cuniculi genotype III, reaching 1.0×10 7 spores per gram of tissue at 35 DPI, compared to 2.4×10 5 and 5.0×10 5 reported in genotypes I and II, respectively (present study), 48 ( Figure 3A ). This correspond to the data published by Sak et al 55 , 58 , 72 and Kotková et al, 49 , 71 ie, the infection intensity of E. cuniculi genotypes I and II was comparable, whereas E. cuniculi genotype III reached up to two orders higher spore burden.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…In SCID mice the concentration of microsporidia was the most intense in E. cuniculi genotype III, reaching 1.0×10 7 spores per gram of tissue at 35 DPI, compared to 2.4×10 5 and 5.0×10 5 reported in genotypes I and II, respectively (present study), 48 ( Figure 3A ). This correspond to the data published by Sak et al 55 , 58 , 72 and Kotková et al, 49 , 71 ie, the infection intensity of E. cuniculi genotypes I and II was comparable, whereas E. cuniculi genotype III reached up to two orders higher spore burden.…”
Section: Discussioncontrasting
confidence: 40%
“… 61–63 Recently, a role for the involvement of such immune cells connected with pro-inflammatory immune responses (eg, trafficking macrophages and other phagocytic cells such as neutrophils, monocytes, dendritic cells, and eosinophils) in the expansion of E. cuniculi infection in host tissues has been suggested based on the occurrence of microsporidia in inflamed tissues 47 and the targeted migration seen following experimental induction of inflammation towards inflammation foci. 48 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, microsporidia could persist and replicate inside macrophages and in this form, they can be transported throughout the host ( 22 ). Brdíčková et al ( 23 ) have shown that other microsporidial species, E. cuniculi genotype II, migrates to inflammatory foci probably with the contribution of immune cells participating in its formation ( 23 ). If this is the case in patients suffering from chronic inflammatory process, subsequent worsening of the IBD clinical picture might occur.…”
Section: Discussionmentioning
confidence: 99%